Enhancing Security in Modern Transposition Ciphers Through Algorithmic Innovations and Advanced Cryptanalysis - Armah, Albert; Asare, Samuel; Abrefah-Mensah, Eric (The Indonesian Journal of Computer Science, 2024)
Abstract Columnar transposition ciphers have various vulnerabilities and limitations that render them vulnerable to modern cryptographic threats and advanced cryptanalysis techniques. It is imperative to strengthen the security of these ciphers through algorithmic developments and a greater understanding of their vulnerabilities as the need for secure communication increases. A systematic search will be conducted to find peer-reviewed journal articles on columnar transposition ciphers, including variations, weaknesses, and security enhancements. The structured data analysis approach will focus on key elements such as known cipher variants, vulnerabilities, new algorithms, proposed improvements, and evaluation metrics. The review will provide a comprehensive overview of the existing variants of columnar transposition ciphers, including the classical columnar transposition cipher, double columnar transposition cipher, mutable columnar transposition cipher, route transposition cipher. It will critically analyze the vulnerabilities and limitations of these variants, such as limited key space, patterns and periodicities, lack of diffusion, and susceptibility to known-plaintext attacks and statistical analysis. Additionally, the review will explore modern cryptographic threats and advanced cryptanalysis techniques, including machine learning, brute force attack, differential cryptanalysis, and chosen plaint-text attack etc. New algorithmic advancements will be developed to enhance the security of columnar transposition ciphers. These advancements involve dynamic key generation, column permutation, integration with other cryptographic primitives, and key scheduling algorithms. Additionally, an enhanced version of the columnar transposition cipher algorithm will be detailed, covering its mathematical basis, theoretical structure, and anticipated security upgrades. The effectiveness of the improved algorithm will be assessed in various attack scenarios and threat models, emphasizing security, computational, and performance aspects. The research will enhance the security of columnar transposition ciphers through algorithmic innovation and advanced cryptanalysis. It will identify gaps in existing techniques, recommend future research directions, and highlight potential applications. The findings will have significant implications for cryptography, addressing the need for secure communication.